Survey on key revocation mechanisms in wireless sensor networks. (March 2016) - Ge, Mengmeng; Choo, Kim-Kwang Raymond; Wu, Huai; Yu, Yong
Abstract: As sensor nodes are deployed in an open and hostile environment, they are vulnerable to various attacks. Due to the insecure nature of the environment, it is of critical importance to be able to revoke compromised nodes to ensure the confidentiality of data traversing in the network. Several approaches to resolving the challenges associated with key revocation have been proposed in the past years, which can be broadly categorized into four main classes, namely centralized, distributed, decentralized and hybrid. In this survey, we present an overview of existing key revocation schemes for wireless sensor networks, as well as a comparative summary (e.g. performance and security features). We also investigate rekeying schemes which are not designed for wireless sensor networks. We conclude this paper with a discussion of open research issues.